2013
DOI: 10.1016/j.jcps.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

When up brings you down: The effects of imagined vertical movements on motivation, performance, and consumer behavior

Abstract: Previous embodied cognition research suggests that “up” is associated with positivity (e.g., good, divine), whereas “down” is associated with negativity (e.g., bad, evil). We focus on the effect of vertical movements on consumer behavior and go beyond investigating mere affective associations of verticality. In five studies, we provide evidence that the mental simulation of vertical movements has counterintuitive effects on behavior—that is, imagining moving up hampers motivation and performance by boosting se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 52 publications
0
34
1
13
Order By: Relevance
“…Which of these diverse meanings of verticality is recruited at a given point in time is likely to depend on its relative accessibility and applicability to the task at hand, consistent with general principles of the context‐sensitive construal of meaning (for a general review, see Schwarz, 2010). Ostinelli, Luna, and Ringberg (2014‐‐in this issue) draw on the association of verticality and valence. Consistent with earlier research, they observe that imagining upward movement has positive evaluative consequences, in their case by boosting feelings of self‐worth.…”
Section: Sensory Experience Mental Simulation and Stimulus Attributesmentioning
confidence: 99%
“…Which of these diverse meanings of verticality is recruited at a given point in time is likely to depend on its relative accessibility and applicability to the task at hand, consistent with general principles of the context‐sensitive construal of meaning (for a general review, see Schwarz, 2010). Ostinelli, Luna, and Ringberg (2014‐‐in this issue) draw on the association of verticality and valence. Consistent with earlier research, they observe that imagining upward movement has positive evaluative consequences, in their case by boosting feelings of self‐worth.…”
Section: Sensory Experience Mental Simulation and Stimulus Attributesmentioning
confidence: 99%
“…Empirically, Ostinelli et al. 's () finding that imagining upward movements makes people feel more self‐worth supports the association between elevation and power.…”
Section: Theoretic Background and Hypothesesmentioning
confidence: 95%
“…For example, Meier and Robinson (, ) found that people categorize positive (vs. negative) words more quickly when shown in the upper (vs. lower) part of a screen, thereby demonstrating a link between vertical positioning and affect. Ostinelli, Luna, and Ringberg () showed that imagining upward movements makes people feel more self‐worth, which undermines their motivation and worsens their performance on a subsequent task. This study suggests not only a link between verticality and power, but also a mediating role of power in the relationship between verticality and task performance.…”
mentioning
confidence: 99%
“…The present research aims to shed light on these issues by investigating whether consumer preference for animated logos depends on logo movement directions and trajectories, as people may associate more or less positive feelings to real life objects moving in specific directions or with specific trajectories which are likely to convey specific meanings to consumers (cf. Ostinelli, Luna, & Ringberg, 2014). To the best of the authors' knowledge, real movement directions have never been examined in relation to animated logos.…”
Section: Mobile Marketing and The Role Of Logo Movement Directionsmentioning
confidence: 99%